Questioning Best Practices with an Innovative Pedagogical Design for Professional Development of Teacher Educators - Karunanayaka, Shironica; Gunawardena, Chandra; Naidu, Som; Lekamge, Dayalatha; Menon, Mohan (INTI International University, 2007)
Best practices in any field of study utilize methodologies that have been proven as reliably leading to desired outcomes, while adding an appreciable value to the experiences of various stakeholders and enhancing the quality of the process. The master of arts in teacher education-international (MATE-I) programme of the open university of sri lanka adopted an innovative pedagogical design, namely Scenario-based Learning (SBL) to promote best practices in the professional development of teacher educators. SBL is a unique learning design, grounded in the principles of constructive pedagogy. It is based on fundamental principles of meaningful learning which include established best practices in teaching and learning such as learning by doing, problem-solving, situated learning, scaffolding of learning and authentic assessment tasks. It also supports collaborative learning and critical reflection while students are supported with various resources including Information and Communication Technologies. While use of an innovative pedagogical design in the MATE (I) programme is expected to lead to best practices, there are several concerns about how it might work in particular educational settings. These include barriers posed by limited English language competency of students and their insufficient background knowledge which may obstruct active participation of leaners. Facilitating interactive sessions is also a demanding and challenging task for the teacher. The expected changes in the roles of teachers and students may be difficult with both parties, who are more comfortable with conventional teacher-centered methods. Although the learners might find the programme more practical, their grounding in the theoretical foundations of the subject matter may be inadequate, if careful attention is not paid to this. The workload of SBL with countinuous learning and assessment activities and online methods poses challenges to students. The outcomes of such and innovative programme may be quite rewarding, yet there is a possibility that it might not be received with enthusiasm by some at least in the early stages of its implementation. However, there is some hope that with the emerging trend in society towards more emphasis on general transferable skills rather than narrow academic specialization, the MATE (I) programme stands to make a significant contribution to the development of such skills in our learners.